TERDISKREDITNYA BAHASA INDONESIA OLEH PENGGUNAAN JUDUL BERBAHASA ASING DALAM PERFILMAN INDONESIA - Oktaviani, Ai Siti; Lestari, Andini Puji; Permana, Aditya (IKIP Siliwangi, 2018)
The Indonesian film industry is now showing its developmental trajectory. Evidenced by the increasing all aspects that encourage the interest of the audience, both in terms of film content and technology used. This study aims to provide information, that in addition to Indonesia's growing and quality films and can be received both at home and abroad, it is even discredited by the use of foreign language titles. Of course, this becomes an irony given that the Indonesian language is not only limited to communication tools, but also as the identity of the nation. The method used in this research is the descriptive qualitative method with data collection technique in the form of the questionnaire. Based on the results of the study, it can be concluded that the interest of the community against the film with the title of Indonesia lacks a place in the hearts of people for various reasons.